Approximate solution of nonlinear differential system with time variation (Journal of Bangladesh Academy of Sciences, 2021)
this paper develops a reliable algorithm based on the general Struble’s technique and extended KBM method for solving nonlinear differential systems. Moreover, we find a solution based on the KBM and general Struble’s technique of nonlinear autonomous systems with time variation, which is more powerful than the existing perturbation method. Finally, results are discussed, primarily to enrich the physical prospects, and shown graphically by utilizing MATHEMATICA and MATLAB software.Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 121-130, 2020